On the Coherence of Mencius’ Concept of Li: An Analysis Based on Moral Reasons Internalism - Shuwen Liu; Xiaodong Xie (Religions, 2023)
This paper addresses the problem of coherence, i.e., whether the internal and external dimensions of li (礼 rituals, rites, and the observance of them) are compatible. This problem stems mainly from Mencius’ seemingly conflicting statements. On the one hand, he emphasized the goodness of xing (性 human nature) in terms of the goodness of the heart-mind. On the other hand, he defended the act of following li regardless of one’s heart-mind. This paper argues that Mencius held coherent moral reasons internalism, asserting that moral reasons are embedded in people’s universal and potential instinct to do morally good things. Consequently, he distinguished morality from non-moral normativity and claimed that the former takes precedence over the latter. The concept of li is thus divided into moral li and non-moral li, with moral li taking precedence over non-moral li. Therefore, the act of “following li regardless of one’s heart-mind” refers to following non-moral li, as long as it does not conflict with moral li. Based on the fact that Mencius’ concept of li is a kind of coherent moral reasons internalism, this paper further responds to some challenges from moral reasons externalism. It does so by clarifying the meaning of “seeking the cause within oneself” (反求诸己 fan qiu zhu ji), showing that Mencius believed every individual could establish rational inner guidance and be motivated to lead a reflective and autonomous moral life.